2013
DOI: 10.1093/ndt/gft327
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxidative stress induces spatial working memory dysfunction in uremic mice: neuroprotective effect of tempol

Abstract: The present study provided evidence that uremia is associated with spatial working memory dysfunction in mice and that treatment with TMP protects against cerebral oxidative stress and improves cognitive dysfunction in uremic mice, suggesting their potential usefulness for the treatment of cognitive dysfunction in uremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…Telmisartan was dissolved in 1 mL of 1 N sodium hydroxide and neutralized by 1 N hydrochloric acid (HCl), then administered for 8 weeks at 0.5 mg/kg/day in drinking water. Blood pressure was measured using the indirect tail-cuff method with a blood pressure monitor (MK-2000; Muromachi Kikai Co., Tokyo, Japan), as described previously (Fujisaki et al, 2014).…”
Section: Preparation Of Micementioning
confidence: 99%
See 1 more Smart Citation
“…Telmisartan was dissolved in 1 mL of 1 N sodium hydroxide and neutralized by 1 N hydrochloric acid (HCl), then administered for 8 weeks at 0.5 mg/kg/day in drinking water. Blood pressure was measured using the indirect tail-cuff method with a blood pressure monitor (MK-2000; Muromachi Kikai Co., Tokyo, Japan), as described previously (Fujisaki et al, 2014).…”
Section: Preparation Of Micementioning
confidence: 99%
“…We recently reported that brain oxidative stress has a major role in spatial working memory dysfunction in a mouse model of chronic Life Sciences 113 (2014) [55][56][57][58][59] uremia (Fujisaki et al, 2014). In that study, treatment with an antioxidant, tempol, readily prevented memory dysfunction and neuronal damage of the hippocampus in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these findings contradict some animal studies describing decreased locomotor activity, exploratory and emotional-like types of behavior in CKD of rodents [17,33]. On the other hand, Fujisaki et al [16] did not reveal decrease in physical performance of CKD rats. In different study, CKD mice manifested decreased anxiety level presented as longer time spent in the light part of light/dark box [18].…”
Section: Discussionmentioning
confidence: 57%
“…Observed central sympathetic overactivity, activation of dorsal raphe serotoninexpressing neurons, histamine-expressing neurons in the hypothalamic tuberomamillary nucleus, those in the prefrontal and anterior cingulate cortex and stress-related brain areas and nuclei might be implicated in affecting (among others) attention, memory processing, cognition, learning and synaptic plasticity. However, current experimental studies regarding behavioral changes in CKD show some controversies [16]. For example, in adenine-induced CKD model in rats decrease in motor activity and increase in depression-like behavior were reported [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation